Rhizobium tibeticum activated with a mixture of flavonoids alleviates nickel toxicity in symbiosis with fenugreek (Trigonella foenum graecum L.) - Abd-Alla, Mohamed Hemida (Ecotoxicology (London, England), 2014)
The objective of this study is to explore the response of an activated Rhizobium tibeticum inoculum with a mixture of hesperetin (H) and apigenin (A) to improve the growth, nodulation, and nitrogen fixation of fenugreek (Trigonella foenum graecum L.) grown under nickel (Ni) stress. Three different sets of fenugreek seed treatments were conducted, in order to investigate the activated R. tibeticum pre-incubation effects on nodulation, nitrogen fixation and growth of fenugreek under Ni stress. Group (I): uninoculated seeds with R. tibeticum, group (II): inoculated seeds with uninduced R. tibeticum group (III): inoculated seeds with induced R. tibeticum. The present study revealed that Ni induced deleterious effects on rhizobial growth, nod gene expression, nodulation, phenylalanine ammonia-lyase (PAL) and glutamine synthetase activities, total flavonoids content and nitrogen fixation, while the inoculation with an activated R. tibeticum significantly improved these values compared with plants inoculated with uninduced R. tibeticum. PAL activity of roots plants inoculated with induced R. tibeticum and grown hydroponically at 75 and 100 mg L(-1) Ni and was significantly increased compared with plants receiving uninduced R. tibeticum. The total number and fresh mass of nodules, nitrogenase activity of plants inoculated with induced cells grown in soil treated up to 200 mg kg(-1) Ni were significantly increased compared with plants inoculated with uninduced cells. Plants inoculated with induced R. tibeticum dispalyed a significant increase in the dry mass compared with those treated with uninduced R. tibeticum. Activation of R. tibeticum inoculum with a mixture of hesperetin and apigenin has been proven to be practically important in enhancing nodule formation, nitrogen fixation and growth of fenugreek grown in Ni contaminated soils